Aquatic indirect photochemical transformations of natural peptidic thiols: impact of thiol properties, solution pH, solution salinity and metal ions. Issue 12 (1st November 2017) - Chu, Chiheng; Stamatelatos, Dimitrios; McNeill, Kristopher
Abstract : Natural peptidic thiols are susceptible to sensitized photodegradation. Abstract : Natural peptidic thiols play numerous important roles in aquatic systems. While thiols are known to be susceptible to sensitized photoreaction, the photochemical transformation of thiols in surface waters remains largely unknown. This study systematically assessed the photochemical transformation of naturally occurring thiols, including arginylcysteine (RC), γ-glutamylcysteine (γEC), glutathione (GSH), and phytochelatin (PC) in solutions containing dissolved organic matter (DOM). The results show that all thiols underwent rapid indirect photochemical transformation. The transformation rates of thiols were highly pH-dependent and increased with increasing solution pH. γEC and GSH show lower transformation rates than free Cys, which was ascribed to their higher thiol p K a values. In comparison, PC and RC show much higher transformation rates than γEC and GSH, due to more reactive thiol groups contained in the PC molecule and sorption of RC to DOM macromolecules, respectively. While all investigated pathways contributed to thiol transformation, hydroxyl radical-mediated oxidation dominated at low solution pH and singlet oxygen-mediated oxidation dominated at high solution pH in the DOM-sensitized phototransformations of γEC, GSH, and PC. Furthermore, the effects of metal complexation and solution salinity on thiol transformation rates were examined. Thiol reactivity was not affected by Fe 3+ and Ag +, slightly enhanced in the presence of Zn 2+, Cd 2+ and Hg 2+, and significantly enhanced by Cu 2+ . Additionally, enhanced thiol transformation rates were observed in solutions with high salinity.